1H-15N NMR correlation study of reaction products of some 3-amino-1H,3H-quinoline-2,4-diones with urea - Lyčka, Antonín; Klásek, Antonín; Kořistek, Kamil; Holčapek, Michal (Univerzita Pardubice, 2005)
Considerably different reaction products in high yields were obtained by reaction of substituted 3-amino-1H,3H-quinoline-2,4-diones with urea in acetic acid depending on substituents in possition 1 and positions 3. 1H-155N NMR correlation spectra were of prime importance in structure elucidation of reaction products formed. Gradient selected 1H-15N HMBC spectra of typical reaction products are shown and discussed.
Keywords: reakční produkty; nukleární magnetická rezonanční spektroskopie; korelace